FAIR ADCP data with OSADCP: a workflow to process ocean current data from vessel-mounted ADCPs - Robert Kopte; Marius Becker; Tim Fischer; Peter Brandt; Gerd Krahmann; Maximilian Betz; Claas Faber; Christian Winter; Johannes Karstensen; Gauvain Wiemer (Frontiers in Marine Science, 2024)
This paper presents the open-source Python software OSADCP developed for the processing of vessel-mounted Acoustic Doppler Current Profiler (VMADCP) data. At this stage, the toolbox is designed for processing VMADCP measurements from open-ocean applications of Teledyne RDI Ocean Surveyor ADCPs and the data acquisition software VMDAS . Based on the VMDAS ENX binary output format, the software contains implementations for cleaning and vector-averaging of single-ping velocity data, verification of the position data, and applying misalignment and amplitude corrections. The procedures of OSADCP are described in detail to encourage the scientific community to use it for their own purposes. The toolbox is an integral part of a workflow implemented on the German marine research vessels in the framework of the Underway Research Data project of the German Marine Research Alliance (DAM). It aims to ensure standardized data acquisition measures, reliable data transfer from the ADCP to shore both near-real-time and in delayed-mode, processing and quality control, and dissemination of the curated data product in the data repository PANGAEA . From PANGAEA , data sets are forwarded to the European marine data hubs Copernicus Marine Service and EMODnet . The workflow that forms the framework for OSADCP is described here as an example of scientific data management that follows the FAIR data guidelines.